Pengaruh Media Big Book Terhadap Kemampuan Membaca Permulaan Pada Siswa Kelas II UPTD SD Negeri 122358 Pematang Siantar - Adelaide Sidabutar; Yuliana Sinaga; Osco P. Sijabat (Journal on Education, 2024)
This research aims to determine whether there is an influence of big book media on the beginning reading abilities of class II students at UPTD SD NEGERI 122358 Pematang Siantar. This research uses quantitative research, a pre-experimental design method using the one group Pretest-Posttest type. The sample in this study was all class II UPTD students at SD Negeri 122358 Pematangsiantar, totaling 24 students. The instruments used in this research were documentation and questionnaires. The technique used in this research is the Normality test and Hypothesis Test (t-test). The results of this research show tcount = 8.735 and ttable= 2.069. From these results it can be seen that tcount>ttable is (8.735>2.069). This means that Ha is accepted, so a decision can be drawn that there is a significant influence of Big Book media on the beginning reading ability of class II UPTD students at SD Negeri 122358 Pematangsiantar.